Association of HCV Prior Infection and Unprotected Sex on Subsequent HIV Acquisition Risk in the Era of Treatment as Prevention - Chen, Fangfang; Tang, Houlin; Han, Juan; Li, Dongmin; Li, Peilong; Wang, Ning; Han, Mengjie; Wang, Lan; Wang, Lu (Frontiers in Medicine, 2022)
Backgrounds: Little was known about the impact of HCV prior infection on HIV transmission and acquisition. We aimed to explore whether HCV prior infection and its interactions with unprotected sex had effect on HIV acquisition. Methods: This study was conducted among HIV heterosexual discordant couples whose index cases receiving treatment during 2008-2014 in Zhumadian. At baseline, we collected information on demographics and medical history of ART use, CD4 count and HIV viral load for index partners, and also HIV and HCV status for nonindex partners. For each year visit, we followed up sexual behaviors among couples in the recent year and HIV seroconversion of nonindex partners. Analysis of Cox model and synergistic interaction were performed. Results: We identified 81 HIV seroconversions over 18370.39 person-years, with the overall HIV seroconversion rate of 0.44 per 100 person-years. Couples whose index cases aged 50 years and above, had baseline viral load >400 copies per ml and no AIDS-defining illness, and newly initiated ART in the study period had higher risk of HIV seroconversion. Unprotected sex and HCV prior infection showed a synergistic association with HIV acquisition risk (RERI=3.65, SI=0.48, AP=2.24). Conclusions: Unprotected sex and HCV infection were independent risk factors associated with HIV acquisition. The coexistence of them might have synergistic effect on the risk which need further research.